(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Development is amulti-dimensional approach. It has played a significant role to establish andpromote the dignity of man. Various thinkers have advocated the concept ofdevelopment. Mahatma Gandhi is one of those distinguished personalities inhuman history whose ideas would be incalculable value. He enunciated aphilosophy of development.